Penguatan Wawasan Kebangsaan dan Nasionalisme di Kelurahan Sidodadi Kota Surabaya - Imam Zarkachi; Adli Hazmi; Moch. Mubarok Muharam; Agus Satmoko Adi; Silkania Swarizona; Eko Satriya Hermawan; Mochamad Arif Affandi (Lembaga Pengembangan Kinerja Dosen, 2024)
Strengthening national insight and nationalism is a strategic step in building a society that loves its homeland, upholds unity, and understands diversity as the strength of the nation. This article discusses a community service program carried out in Sidodadi Village, Surabaya City, with the aim of increasing public understanding of national insight and nationalism. This program involved 30 participants from various backgrounds through seminars, group discussions, and practical training. Participatory methods were applied to ensure active community involvement in the learning process. The evaluation results showed a significant increase in the level of participant understanding, from 70% before the activity to 85% after. In addition, the positive response from participants reflects the success of this activity in instilling national values ​​that are relevant to everyday life. Despite challenges such as time constraints and uneven involvement, this activity has had a real impact on strengthening nationalism at the local level. This program concludes that strengthening national insight requires a systematic, educational, and sustainable approach. With the support of local governments and community participation, similar activities can be replicated in other regions to strengthen national unity.